PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP SELF-ESTEEM PESERTA DIDIK KELAS VIII DI SMPN 1 LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Mita Putri Regina Margareta Manalu; Rici Kardo; Wira Solina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescence is a transitional period where individuals begin to seek their identity and are heavily influenced by their social environment. Self-esteem is a crucial aspect of adolescent development that often fluctuates, and peer social support is presumed to be one of its determining factors. This study aims to determine whether there is a significant influence of peer social support on the self-esteem of eighth-grade students at SMPN 1 Luhak Nan Duo, West Pasaman Regency. This study employed a quantitative approach using a simple regression design. The population consisted of 229 eighth-grade students, with a sample of 146 selected through proportional random sampling. The research instruments were peer social support and self-esteem questionnaires. Data were analyzed using descriptive statistics and simple regression analysis. The results showed that peer social support was in the fairly good category, while students’ self-esteem was in the moderate category. The regression analysis indicated that peer social support had a significant effect on students’ self-esteem. These findings suggest that higher peer social support contributes to higher levels of self-esteem among students. Therefore, peer social support plays an important role in enhancing students’ self-esteem and should receive attention from schools, particularly guidance and counseling services. Keywords: Social support, peer, self-esteem, students